Social Identity Represented in Dai’s Discourse - Rangkuti, Rahmadsyah; Sinar, T. Silvana; Setia, Eddy; Zulfan, Mulyadi (KnE Social Sciences, 2019)
This research is motivated by the use of language as a marker of da’is (preachers) identity and ideology in the city of Medan represented in their preaching. The outbreak of the spirit of Islam which was marked by the proliferation of Islamic da’wah forums in urban areas, presented a treasure of language problems that could be used as new objects of linguistic analysis. In the discourse of Islamic preaching, language plays an important role that could be used to portray a personal and sociocultural identity of a dai. Even the use of language can also represent the ideology of the dai. The purpose of this study is to find out the linguistic features that shape identity and the ideology represented in the preaching discourse of Dai in the city of Medan. Practically, a phenomenological design was used in this study based on a critical socio-pragmatic approach. The data are in the form of speech collected purposively and analyzed by distributional and contextual method and presented formally and informally. Keywords: identity, ideology, discourse, urban areas, da’i.